2017
DOI: 10.1021/acsami.7b14992
|View full text |Cite
|
Sign up to set email alerts
|

Mucus and Cell-Penetrating Nanoparticles Embedded in Nano-into-Micro Formulations for Pulmonary Delivery of Ivacaftor in Patients with Cystic Fibrosis

Abstract: Here, mucus-penetrating nanoparticles (NPs) for pulmonary administration of ivacaftor in patients with cystic fibrosis (CF) were produced with the dual aim of enhancing ivacaftor delivery to the airway epithelial cells, by rapid diffusion through the mucus barrier, and at the same time, promoting ivacaftor lung cellular uptake. Pegylated and Tat-decorated fluorescent nanoparticles (FNPs) were produced by nanoprecipitation, starting from two synthetic copolymers, and showed nanometric sizes (∼70 nm), a slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 47 publications
(111 reference statements)
0
66
0
Order By: Relevance
“…This is used to synthesize other different colloidal nanoparticles made up of organic or hybrid materials. These colloidal nanoparticles have a negative Z-potential, as has been previously reported [41,42,43,44,45,46], and the value of the negative charge depends on the medium in which the colloidal nanoparticles are diluted/dispersed, before the analysis, as well as other components of the pharmaceutical formulations [47,48,49,50,51,52,53,54].…”
Section: Resultsmentioning
confidence: 63%
“…This is used to synthesize other different colloidal nanoparticles made up of organic or hybrid materials. These colloidal nanoparticles have a negative Z-potential, as has been previously reported [41,42,43,44,45,46], and the value of the negative charge depends on the medium in which the colloidal nanoparticles are diluted/dispersed, before the analysis, as well as other components of the pharmaceutical formulations [47,48,49,50,51,52,53,54].…”
Section: Resultsmentioning
confidence: 63%
“…4d), which confirmed that bare PLGA and PLGA-PVA NPs are more likely to bonds with mucin. Likewise, turbidity measurements and mucin absorption percentage were also performed to investigate the interaction between NPs and mucin [41][42][43] ( Supplementary Fig. 5a and 5b), which altogether pointed to the fact that PLGA-PEG and PLGA-PDA NPs interacted much less with mucin than those of bare PLGA and PLGA-PVA NPs.…”
Section: Exploration Of the Interaction Mechanisms Between Pva-dopa Fmentioning
confidence: 98%
“…between NPs and the mucin particles 40 . Here, we first examined the ability of different NPs to adsorb mucin by probing the variation in average particle size and zeta-potential of NPs 40,41 . When mixed with mucin suspension, bare PLGA and PLGA-PVA NPs showed a significant larger increase in average size compared with PLGA-PEG and PLGA-PDA NPs (Fig.…”
Section: Exploration Of the Interaction Mechanisms Between Pva-dopa Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In this latter case, patients treated with these drugs experienced severe systemic side effects and to boost their efficacy the drugs concentration and their permanence at the lungs, the major site of disease, should be improved. The pulmonary administration of CFTR modulators based on mucus penetrating NPs could be an effective strategy, potentially increasing higher local drug concentrations and minimizing side effects when compared to the oral route of administration (Porsio et al, 2018).…”
Section: Conclusion and Future Remarksmentioning
confidence: 99%